2005
DOI: 10.1016/j.rmed.2004.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the accuracy of peak flow meters: a double-blind study using formal methods of agreement

Abstract: There was a significant difference between the values obtained from the new and old peak flow meters and also between the two new peak flow meters. We conclude that there is need for caution in interchangeably using flow meters in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Whereas this study did utilize human subjects, the use of a qualified examiner and of standard verbal commands assured that the effort demanded during the PEF measurement was the subject’s maximum and was similar for all of the meters. According to Nazir et al14 and Pretto et al (and cited by Koyama et al8), despite the fact that measurements obtained with human subjects may be less accurate than those made with flow generating equipment, it has been suggested that the measurements obtained with human subjects are more clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this study did utilize human subjects, the use of a qualified examiner and of standard verbal commands assured that the effort demanded during the PEF measurement was the subject’s maximum and was similar for all of the meters. According to Nazir et al14 and Pretto et al (and cited by Koyama et al8), despite the fact that measurements obtained with human subjects may be less accurate than those made with flow generating equipment, it has been suggested that the measurements obtained with human subjects are more clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Many different studies have focused on testing the accuracy of these meters by comparing devices from different manufacturers and equipments from the same brand; these studies have revealed significant inter- and intra-meter variations 1,5,7,8,11–14. In these studies different methods were used to evaluate the accuracy of the peak flow meters, such as a flow generator acknowledged and recommended by the American Thoracic Society (ATS), the collaboration of individuals generating flow in a spirometer connected in series to the meters, or to separate the performance of spirometry measurements with several peak flow meters, with subsequent comparison of the results.…”
Section: Introductionmentioning
confidence: 99%
“…One important caveat is that some of these portable devices may not be as accurate or consistent or reproducible with results as reproducible as the more expensive equipment available in the clinician's office. [62][63][64] In addition, measurements made with devices that record numerical values for FEV 1 but do not record full flow-volume curves are subject to possible misinterpretation if the patient has laryngeal dysfunction.…”
Section: Evaluation Of Eiamentioning
confidence: 99%
“…The application of multiple or a combination of methods, particularly in the assessment of agreement, suggests that there is no consensus among researchers on which method is the best statistical method for measuring agreement. One example of the multiple application of method is in one study that testing the accuracy of peak flow meters [24]. In this study, the authors applied three statistical methods (Pearson's correlation coefficient, comparing mean (significant test) and the Bland-Altman method) to assess for agreement of peak flow meters [24].…”
Section: Application Of Multiple Methodsmentioning
confidence: 99%
“…One example of the multiple application of method is in one study that testing the accuracy of peak flow meters [24]. In this study, the authors applied three statistical methods (Pearson's correlation coefficient, comparing mean (significant test) and the Bland-Altman method) to assess for agreement of peak flow meters [24].…”
Section: Application Of Multiple Methodsmentioning
confidence: 99%